Facilitators of and barriers to participation in Long COVID research: A qualitative analysis - Lily Chu; Theodore Lucas Hollar; Nancy Klimas; Jeanne Bertolli; Ana Lia Tamariz; Aryan Lajevardi; Ilya Pavlov; Ana Palacio (PLoS ONE, 2026)
Background Meeting recruitment targets in an expeditious manner is essential to the successful completion of any research project. However, despite the high prevalence and debilitating nature of Long COVID (LC), recruitment of participants into some LC studies has been challenging. Objective We aimed to a) identify factors influencing participation in LC research among individuals who were infected by SARS-CoV-2 but had declined participation in a LC study and b) to compare these factors to those previously recognized. Methods Using a semi-structured guide, we interviewed thirteen people about their thoughts, experiences, and attitudes concerning participation in LC research. We imported interview transcripts into Nvivo 14 and analyzed them using thematic analysis. For coding, we used Charmaz’s coding scheme of open and focused coding within an application of the constant comparative method. Basic descriptive statistics were also deployed to supplement our qualitative analysis. Results Fifteen factors describe the facilitators and barriers mentioned by participants. The top three facilitators were Personal and social motivation, Incentives, and Familiarity and credibility of institutions involved with COVID-19 ; the top three barriers were Invasiveness, Social and political context, and Lack of time . Skepticism and infringement on participants’ daily lives served as major obstacles to participation while trust, personal factors, and administrative factors encouraged participation. The facilitators and barriers identified are similar to those recognized previously except that in the politically charged atmosphere surrounding the COVID-19 pandemic, trust was especially vital. Conclusions Many factors affect people’s decisions to participate in LC research but only some are modifiable by researchers. Building trust, offering incentives participants value, and removing logistical barriers may improve recruitment rates.